A Novel Technique of Laparoscopic Transabdominal Cerclage after a Mersilene Tape Erosion in a Prior Laparoscopic Radical Trachelectomy and Transvaginal Cerclage Patient - Jhanice Paredes; Kuan-Gen Huang; Chyi-Long Lee; Gillian Patrick Gonzalez; Mary Evangeline Mercado; Zin Mar Lay (Wolters Kluwer Medknow Publications, 2024)
A case of a 32-year-old patient who presented with vaginal bleeding 2 years after undergoing laparoscopic radical trachelectomy and vaginal cerclage was noted to have Mersilene tape erosion. Subsequent management includes the removal of displaced Mersilene tape and a repeat cerclage through a new technique of laparoscopic abdominal cerclage to avoid repeat tape erosion. The novel technique of laparoscopic abdominal cerclage to lower the incidence of preterm delivery among pregnant patients who underwent laparoscopic radical trachelectomy for early-stage cervical cancer is described.